![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x2-3x-x+3>0
<=> x(x-3)-(x-3)>0
<=> (x-3)(x-1)>0
\(\left[{}\begin{matrix}\left\{{}\begin{matrix}x-3>0\\x-1>0\end{matrix}\right.\\\left\{{}\begin{matrix}x-3< 0\\x-1< 0\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x>3\\x>1\end{matrix}\right.\\\left\{{}\begin{matrix}x< 3\\x< 1\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x>3\\x< 1\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) = 3( x2 + 2x/6 + 1/9) + 6 -1/3 =3(x+ 1/3)2 + 17/3 >0 (dpcm)
![](https://rs.olm.vn/images/avt/0.png?1311)
a , Ta có \(x^2+x+1=x^2+2x\frac{1}{2}+\left(\frac{1}{2}\right)^2+\)\(\frac{3}{4}=\left(x+\frac{1}{2}\right)^2+\frac{3}{4}\) \(\ge\frac{3}{4}>0\left(đpcm\right)\)
b , Ta có : \(4x^2-2x+3\)= \(\left(2x\right)^2-2.2x.1+1^2+2\) = \(\left(2x-1\right)^2+2\ge2>0\left(đpcm\right)\)
c , Ta có \(3x^2+2x+1=x^2-\frac{2x}{3}+\frac{1}{9}+2x^2+\frac{8x}{3}+\frac{8}{9}\)
= \(\left(x-\frac{1}{3}\right)^2+2\left(x^2+\frac{4x}{3}+\frac{4}{9}\right)=\left(x-\frac{1}{3}\right)^2+2\left(x+\frac{2}{3}\right)^2\ge0\)
Vì Dấu "=" không thể xảy ra , do đó \(3x^2+2x+1>0\left(đpcm\right)\)
Ta có: \(x^3-2x^2+3x-6>0\)
\(\Leftrightarrow x^3+3x-2x^2-6>0\)
\(\Leftrightarrow x\left(x^2+3\right)-2\left(x^2+3\right)>0\)
\(\Leftrightarrow x-2>0\)
hay x>2